Optimizing Youth Participation in Maternal and Child Health Issues in Wonosobo Regency: Human-Centered Design-Based Policy Analysis - Fajar Kurniyasih (Spirit Publik: Jurnal Administrasi Publik, 2025)
that is crucial to raishing the standart of living for coming generations. Despite the implementation of numerous program aimed at lowering stunting, infant mortality (IMR) and maternal mortality (MMR), regional issues are still complicated, especially regarding youth participation in promoting the health agenda. Using a Human Centered Design (HCD) approach, this project aims to analyze youth participation in MCH issue and develop policy options based on local requirements. In February 2023, 38 people from variety of groups (youth, pregnant women, heatth works, religious leaders, and community members) participated in an HCD based Forum Dengar Pendapat (FDP) in Wonosobo regency. The data were analyzed using thematic analysis and validated using member checking and source triangulatin. The results of the study revealed five main strategic issues: high rates of child marriage, low knowledge of youth about reproductive health, suboptimal implementation of Respectful Maternity Care, limited access to health insurance, and minimal involvement of community leaders in child health issues. Through the use of the Youth Participation Theory, it was found that youth participation in Wonosobo is still at the symbolic to pluralistic level, but shows potential for improvement towards youth-adult partnership through collaboration mechanisms and policy design for youth. The integration of Youth Participation Theory and HCD in this study contributes theoretically to the development of a transformative participatory health policy model, in which youth a role as co-designers and agents of change in the formulation of public policy. These findings also have practical implications for local governments to strengthen the capacity of youth and create more meaningful spaces for participation, in order to accelerate improvements in maternal and child health at the local level.